Working thematically: changing the path to leadership for the third space - Fiona Denney; Emily McIntosh (Journal of Learning Development in Higher Education, 2025)
What does leadership mean in the third space, and how is it changing?  This opinion piece offers a perspective on third space leadership, through embracing thematic working and drawing together often disparate elements of the academy.  The paper argues that the future workforce of HE depends on third space leadership and that the skills, attributes and opportunities, such as managing “supercomplexity” (Barnett, 2000) and “complex collaboration” (Veles et al, 2019) must be leveraged in order to support and encourage those who already work in this space.  It offers two proposals that would effect the changes necessary to realise this, including looking at different HE contracts and criteria necessary for senior leadership.